2019
DOI: 10.3390/su11133680
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Assets and Strategies Affecting the Forestry Household Income: Empirical Evidence from South Korea

Abstract: This study aims to identify the factors determining the forestry household income in South Korea. An empirical analysis was conducted on the Korea Forest Service’s 3-year-panel data. Korea Forest Service is an institution responsible for the sustainable management of South Korea’s forest lands. In the study, the hypothesized factors determining the forestry household income are classified into four types of assets and three types of livelihood strategies. The forestry household income (FHI) is divided into thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Suppliers are obliged to pay the certification fee for ELF [10]. Most costs will be burdensome for small forest product providers [7]. However, since an ELF can contribute to sustainability, it is worth looking at how certification is delivered to buyers.…”
Section: Demand Side: Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suppliers are obliged to pay the certification fee for ELF [10]. Most costs will be burdensome for small forest product providers [7]. However, since an ELF can contribute to sustainability, it is worth looking at how certification is delivered to buyers.…”
Section: Demand Side: Satisfactionmentioning
confidence: 99%
“…ELF providers may be reluctant to produce ELFs because of the cost of certification. However, if consumers are fully aware of this and intend to purchase, the marketability will require a long-term investment [7,30]. In other words, from a supplier's perspective, the WTP should come up with some solutions to the uncertainty about certification.…”
Section: Demand Side: Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research from Jang-Hwan, Jo et al (2019) conducted research on assets and strategies in managing sustainable forests in South Korea, with the results of research that the correct use of assets and good strategies will have an influence on the income of surrounding communities / Forest Farmer Groups. Some of the aspects of the study are Household Income from Forestry, Income from Forests and Non-Forest Income.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, foreign scholars have gradually started to focus on the research on forest landowners' willingness [8][9][10][11] and behavior [12][13][14][15] to engage in forest management. Price (1997) concluded that factors such as forest land resource endowment and individual farmers' characteristics have a certain degree of influence on the transformation of management behavior and willingness through the forestry production efficiency in the UK [16]; Viitale (1998) found that reducing the input to public benefit forests inputs can appropriately change the generally low technical efficiency of production [17]; Denis J (2011) suggested the importance of policy for developing forestry [18]; Thant (2011) studied the role and influence of willingness and behavior of 200 households in Myanmar on achieving sustainable forestry [19]; Goyke et al (2019) examined the role and influence of the willingness and behavior of 200 households in Myanmar on achieving sustainable forestry through a study of selected US Southern African American forest landowners, they found that professional advice had the greatest degree of influence on forest landowners' participation in forest management behavior [20]; Jang-Hwan conducted a statistical analysis based on panel data from sustainable forest land management institutions in Korea and found that a number of elements related to the livelihood strategy level influenced farm household forestry income to varying degrees, and thus will also affect the willingness to engage in forest management and the sustainability of forestry [21].…”
Section: Introductionmentioning
confidence: 99%